2020
DOI: 10.1007/s13353-020-00563-7
|View full text |Cite
|
Sign up to set email alerts
|

How far musicality and perfect pitch are derived from genetic factors?

Abstract: There is an agreement about joint genetic and environmental background of musical reception and performance. Musical abilities tend to cluster in families. The studies done on a random population, twins and families of gifted musicians provided a strong support for genetic contribution. Modern biomolecular techniques exploring linkage analysis, variation of gene copy number, scanning for whole-genome expression helped to identify genes, or chromosome regions associated with musical aptitude. Some studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
1
11
0
2
Order By: Relevance
“…Consistently, a previous metanalysis, based on 105 molecular studies carried out on humans and other animal species [24], found a top candidate related to music abilities in humans in chromosome 4q21-q24; this region contains seven top candidate genes, namely, MAPK10, SNCA, ARHGAP24, TET2, UBE2D3, FAM13A, and NUDT9.…”
Section: General Musical Abilitiessupporting
confidence: 75%
See 1 more Smart Citation
“…Consistently, a previous metanalysis, based on 105 molecular studies carried out on humans and other animal species [24], found a top candidate related to music abilities in humans in chromosome 4q21-q24; this region contains seven top candidate genes, namely, MAPK10, SNCA, ARHGAP24, TET2, UBE2D3, FAM13A, and NUDT9.…”
Section: General Musical Abilitiessupporting
confidence: 75%
“…Gingras et al [ 9 ] presented a synthesis of literature regarding musicality at the extremes (amusia, AP, and altered musicality in genetic syndromes), as well as genome-wide linkage and association studies of musicality in the general population. The Department of Medical Genetics at the University of Helsinki has made a special contribution to the field, with several genomic studies on musical aptitude, perception, and practice [ 5 , 22 , 23 ], while Szyfter and Witt [ 24 ] recently presented a review study on genetics and musicality. The last review [ 25 ] introduced a stimulating narrative regarding the biocultural origin of music and its evolutionary function.…”
Section: The Genetic Basis Of Music In Human Evolutionmentioning
confidence: 99%
“…Moreover, several studies have been carried out to explicitly identify the genetic basis of musicality and dozens of genes have been so far associated with musical aptitude, as described in other relevant reviews by Oikkonen and colleagues [111], Järvelä [91] and most recently by Szyfter and Witt [162]. With the discovery that FOXP2, the gene previously regarded as the "language gene", shows no prevalent signals of positive selection and is, therefore, not the paramount responsible for language evolution in humans, there is reason to believe that language actually arose as an extremely complex polygenic trait with strong influences from societal structures and cultural practices [163][164][165].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In reality, the Bach family only received training in the profession of musician, which was handed down from father to son and therefore provided a source of income. However, its difficult to explain the existence of seven famous musicians in one family, across generations, one of whom is an acknowledged genius, and at least two more who are extremely well-known, as the result of family practice alone (Szyfter et al, 2020).…”
Section: Inheritance Of Musical Talent In Renowned Artists' Familiesmentioning
confidence: 99%
“…Genes influencing auditory and creative involvement in music have recently been identified using genomewide linkage and association scanning. The primary instruments for detecting gene copy number changes and estimating gene expression are now gene copy number changes and gene expression estimates, and the findings of this research will be given later on (Szyfter et al, 2020).…”
Section: Introductionmentioning
confidence: 99%